2014
DOI: 10.1155/2014/639687
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Grass Carp (Ctenopharyngodon idellus) and Crisp Grass Carp

Abstract: Grass carp (Ctenopharyngodon idellus) is one of the most important freshwater fish that is native to China, and crisp grass carp is a kind of high value-added fishes which have higher muscle firmness. To investigate biological functions and possible signal transduction pathways that address muscle firmness increase of crisp grass carp, microarray analysis of 14,900 transcripts was performed. Compared with grass carp, 127 genes were upregulated and 114 genes were downregulated in crisp grass carp. Gene ontology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…These findings suggested that dietary nutritional factors may affect fish growth by modulating the MRFs expression. Yu et al (2014) indicated that the relative genes expression of muscle differentiation were strongly correlated with muscle firmness of grass carp by using microarray sequencing technique to research the difference between grass carp and crisp grass carp, which was in agreement with the present study. Besides, L. M. Valente et al (2016) reported that dietary incorporation of plant protein would modulate the expression of muscle growth-related genes and would thereby alter muscle cellularity and textural profile of Senegalese sole.…”
Section: Effect Of Partial Substitution Of Fbm For Sbm On Flesh Quasupporting
confidence: 92%
“…These findings suggested that dietary nutritional factors may affect fish growth by modulating the MRFs expression. Yu et al (2014) indicated that the relative genes expression of muscle differentiation were strongly correlated with muscle firmness of grass carp by using microarray sequencing technique to research the difference between grass carp and crisp grass carp, which was in agreement with the present study. Besides, L. M. Valente et al (2016) reported that dietary incorporation of plant protein would modulate the expression of muscle growth-related genes and would thereby alter muscle cellularity and textural profile of Senegalese sole.…”
Section: Effect Of Partial Substitution Of Fbm For Sbm On Flesh Quasupporting
confidence: 92%
“…The proteomic data obtained in the current study indicated that two enzymes involved in the intermediate process of glycolysis were significantly upregulated in the muscle of crisp grass carp, with the protein expression of the aldehyde dehydrogenase 9 family, for example, increasing 87.90-fold. In the expression profile of crisp grass carp, we also found that the gene expression of aldehyde dehydrogenase increased 5.51-fold8. Under anaerobic conditions, aldehyde dehydrogenase can oxidise glyceraldehyde-3-phosphate to 1,3-diphosphoglycerate, and reduce NAD + to NADH.…”
Section: Discussionmentioning
confidence: 62%
“…This study showed significantly decreased protein expression of pyruvate dehydrogenase, which is associated with the decomposition of pyruvate. In our previous study, the gene expression of pyruvate dehydrogenase also decreased 0.15-fold in the crisp grass carp8. This indicated that during muscle hardening of grass carp, pyruvate less efficiently entered the mitochondria, to undergo oxidative decomposition via the citric acid cycle pathway.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations